Around the conjunction of new social movements and identity. Exploring identity politics - Tutor-Antón, Arítz (Revista de Estudios Andaluces, 2024)
This paper approaches identity politics from the genealogy and umbrella offered by the theory of New Social Movements. The aim is to unravel how New Social Movements that put postmaterialist issues such as identity and classic movements that fight for redistributive issues are related, and eventually articulated. This approach is carried out from a theoretical review, so the proposed perspective is developed in the epistemological field, from a qualitative and hermeneutical point of view. The text explores the links between these new forms of collective action and the claim to identity, updating the focus on a political expression that is fully in force and constantly rising. Afterwards, there is a review of the criticisms it has received, relating these to the historical and political context. With an analysis of the critical routes that have delved into the tension between the vindication of the particular and the universal, it seeks to formulate theses that serve to extrapolate and generalize from concrete situations to shared demands. Finally, some political and epistemological solutions are considered that make these struggles compatible with political actions of greater social scope and political impact.